The Impact of Vertebroplasty on Sagittal Parameters in Traumatic Thoracic Vertebral Fractures - Kemal PAKSOY (Modern Medicine, 2023)
Objective: It is well-established that vertebroplasty has effects on sagittal parameters due to various pathologies of the spine. Our objective in the study was to reveal the impact of vertebroplasty that was applied to compression fractures due to trauma on sagittal parameters. Material and Method: Twenty patients were included in the study. Scoliosis radiographs were shot preoperatively and at first month during the postoperative period. Spinopelvic parameters of each patient including pelvic incidence (PI), sacral slope (SS), pelvic tilt (PT), lumbar lordosis (LL), thoracic kyphosis (TK), thoracolumbar kyphosis (TLK), cervical lordosis (CL), and sagittal vertical axis (SVA) were assessed. Visual Analogue Scale (VAS) and Oswestry Disability Index (ODI) assessments of the patients were performed as well. Results: Spinopelvic parameter values of the patients were assessed statistically through the analysis of the Paired sample T test before surgery and in the first month during the postoperative period. It was determined that the changes in the PT, SS and LL values of the patients between preoperative and first month postoperative were at the level of p=0.659, p=0.716, p=0.012; and the changes were not significant. It was determined that the changes in the TL, TK, CL, SVA, VAS and ODI values of the patients between preoperative and first month postoperative were at the level of p <0.001and the changes were significant. Conclusion: Vertebroplasty is an efficient technique for relieving pain in thoracic fractures that have a score of 4 and over, based on the thoracolumbar injury classification score and that are type A, based on the AO Spine thoracolumbar injury classification score. Elimination of pain in the acute period is effective in ameliorating the sagittal parameters of patients.